Penyuluhan Hukum di Kelurahan Tanjung Karang Kecamatan Sekarbela Kota Mataram - Sarudi; Ady Supryadi (BALE LITERASI, 2026)
The purpose of community service activities is to ensure that the community is aware of and understands regulations related to customary law and the potential of Mataram City. This is because the ability of a village head to influence the community is a major factor that determines the direction of development in the village. Furthermore, the village head must also have the ability to explore the village's potential, which will then be identified with several problems that can be influenced to be solved together with all village officials and the community so that the hope of advancing the village can be achieved. Providing education to the village community through legal counseling is also part of an effort to increase public understanding of the importance of legal awareness, both based on laws and regulations and maximizing the financial and administrative accountability system to support the economic sector of Mataram City